2001
DOI: 10.4049/jimmunol.166.3.1627
|View full text |Cite
|
Sign up to set email alerts
|

Rac and Phosphatidylinositol 3-Kinase Regulate the Protein Kinase B in FcεRI Signaling in RBL 2H3 Mast Cells

Abstract: FcεRI signaling in rat basophilic leukemia cells depends on phosphatidylinositol 3-kinase (PI3-kinase) and the small GTPase Rac. Here, we studied the functional relationship among PI3-kinase, its effector protein kinase B (PKB), and Rac using inhibitors of PI3-kinase and toxins inhibiting Rac. Wortmannin, an inhibitor of PI3-kinase, blocked FcεRI-mediated tyrosine phosphorylation of phospholipase Cγ, inositol phosphate formation, calcium mobilization, and secretion of hexosaminidase. Similarly, Clostridium dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 64 publications
5
35
0
1
Order By: Relevance
“…Consistently, antioxidants and DPI diminish Akt phosphorylation in VSMCs in response to angiotensin II, another potent activator of the NADPH oxidase, 28 further supporting the idea that Akt is specifically activated via the NADPH oxidase. Similarly, in rat basophilic leukemic cells, C difficile toxin B has been shown to decrease phosphorylation of Akt but not of ERK1/2 in response to Fc⑀ receptor stimulation, 29 and in murine hematopoietic BaF3 cells, Rac was essentially involved in the activation of Akt and p38 MAP kinase. 30 Because PI 3-kinase inhibitors attenuate TF mRNA expression and Akt phosphorylation in response to thrombin, the NADPH oxidase-mediated activation of the PI 3-kinase/Akt pathway may thus provide a novel mechanism contributing to thrombin-induced TF expression and surface procoagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, antioxidants and DPI diminish Akt phosphorylation in VSMCs in response to angiotensin II, another potent activator of the NADPH oxidase, 28 further supporting the idea that Akt is specifically activated via the NADPH oxidase. Similarly, in rat basophilic leukemic cells, C difficile toxin B has been shown to decrease phosphorylation of Akt but not of ERK1/2 in response to Fc⑀ receptor stimulation, 29 and in murine hematopoietic BaF3 cells, Rac was essentially involved in the activation of Akt and p38 MAP kinase. 30 Because PI 3-kinase inhibitors attenuate TF mRNA expression and Akt phosphorylation in response to thrombin, the NADPH oxidase-mediated activation of the PI 3-kinase/Akt pathway may thus provide a novel mechanism contributing to thrombin-induced TF expression and surface procoagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the activation of Rho GTPases is PI3K-independent in RBL-2H3 cells [24]. PLCc was found to directly bind Cdc42 in vitro in these cells [21], suggesting that PLCc could be a downstream effector of Rho GTPases in response to antigen stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that Rac activation in response to antigen stimulation in mast cells is PI3K-independent [24]. This led us to examine other effectors in the degranulation pathway with regard to Rac and Cdc42 regulation.…”
Section: Plcc Inhibition Increases the Activation Of Rac And Cdc42mentioning
confidence: 99%
See 1 more Smart Citation
“…Le domaine PH, dont la fonction normale est de se lier à certains phospholipides membranaires [9, 10], pourrait jouer un rôle potentialisateur de l'activité des protéines Vav. Cependant, l'activation de Vav par liaison aux phospho-inositides membranaires n'est pas clairement établie et certaines publications récentes définissent une hiérarchie dans laquelle la voie PI-3K est activée en aval ou en parallèle des protéines Vav et de leurs substrats [11,12]. À côté de cette régulation de l'activité catalytique d'échange, la région carboxy-terminale comprenant les domaines SH3-SH2-SH3 joue un rôle adaptateur essentiel en recrutant des molécules de signalisation participant à la régulation de l'activité de Vav.…”
Section: Régulation De L'activité Des Protéines Vavunclassified